Monitoring of the Rolling Mill Vibration - Stefan DRAGOMIR (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2009)
These researches show the influence of mill vibration on the thickness profile of the stainless steel sheet. The alloy elements like Ni and Cr inside the stainless steel could amplify the rolling mill vibration and determine severe damages for rolling sheet. These damages consist in variation of thickness on the length of strip. We made recordings of vibrations during the rolling process and we propose an integrate system for vibration monitoring.